ParIS Genome Rearrangement server. - Miklós, I; Ittzés, P; Hein, J (2005)
SUMMARY: ParIS Genome Rearrangement is a web server for a Bayesian analysis of unichromosomal genome pairs. The underlying model allows inversions, transpositions and inverted transpositions. The server generates a Markov chain using a Partial Importance Sampler technique, and samples trajectories of mutations from this chain. The user can specify several marginalizations to the posterior: the posterior distribution of number of mutations needed to transform one genome into another, length distribution of mutations, number of mutations that have occurred at a given site. Both text and graphical outputs are available. We provide a limited server, a downloadable unlimited server that can be installed locally on any linux/Unix operating system, and a database of mitochondrial gene orders.